Targeting gut-brain-immune axis in amyotrophic lateral sclerosis - Mudda, Naga Sriharsha; Zhang, Lucas; Sampelli, Pooja (Frontiers in Immunology, 2026)
Amyotrophic lateral sclerosis (ALS) is a fatal motor neuron neurodegenerative disorder with a median survival of only 3–5 years. The heterogeneity of the disease and lack of effective therapies highlight the importance of identifying novel pathogenic mechanisms. We hypothesize that dysbiosis of gut microbiota enhances ALS by disrupting intestinal barrier function and altering metabolite profiles to drive systemic inflammation and neuronal stress. Precisely, the decrease in health-promoting bacteria (e.g., Akkermansia muciniphila, Bifidobacterium and Lactobacillus spp.) in ALS can reduce neuroprotective metabolite production (short-chain fatty acids, nicotinamide, GABA, precursors of serotonin) and increase gut permeability, enabling lipopolysaccharide (LPS) and pro-inflammatory cytokines into the circulation. Such changes would activate microglia and impair motor neuron homeostasis by glutamate excitotoxicity and mitochondrial dysfunction. The gut-brain axis operates through immune-mediated mechanisms, where ALS-associated microbiota changes compromise mucosal immunity and trigger peripheral Th1/Th17-biased responses with impaired Treg regulation. Elevated endotoxin levels correlate with TLR4-driven inflammation, promoting pro-inflammatory cytokines (IL-1β, IL-6, TNF-α) that cross into the CNS and prime microglia toward a neurotoxic M1 phenotype, creating a milieu where IL-17A and other mediators directly injure motor neurons. Our hypothesis relies on establishing human and animal evidence of microbiome derangements, barrier dysfunction, and immune deregulation with ALS. We hypothesize that restoration of an “ALS-protective” microbiota consortium or its metabolic by-products can potentially slow disease progression. Testable hypotheses include improvement of ALS model motor deficits by probiotic or fecal-microbiota therapies, and normalization of inflammatory biomarkers. This paradigm recontextualizes ALS as a gut-brain disease and suggests new directions for translational research into this unmet medical indication.